2010
DOI: 10.1136/adc.2009.180786
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions in children in Camaguey Province, Cuba

Abstract: ADRs in children are more frequent than previously reported. A successful pharmacovigilance programme can be established in lower middle income countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…We described the ADRs detected in children in Camagüey Province in 2008 [1]. Although we demonstrated an ADR reporting rate of 634 per million children per year in Cuba, we recognised that this figure was likely to be a significant underestimate of the true rate of ADRs.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…We described the ADRs detected in children in Camagüey Province in 2008 [1]. Although we demonstrated an ADR reporting rate of 634 per million children per year in Cuba, we recognised that this figure was likely to be a significant underestimate of the true rate of ADRs.…”
Section: Introductionmentioning
confidence: 82%
“…For children who experienced more than one ADR, the clinical impact of the separate ADRs was considered together and one severity classification was given. Severity was classified as severe/moderate/mild [1, 11].

severe: fatal or potentially life threatening or causing permanent disability;

moderate: requiring treatment or prolonging stay in hospital or causing interference with normal daily activities;

mild: minor reactions that do not require treatment and do not prolong stay in hospital.

…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, health care professionals may be reluctant to report a suspected ADR if a medicine being used is unlicensed or "off-label", because of potential liability issues [34]. Underreporting is more relevant for ADRs in children, and educational intervention for health professional are effective also in setting characterised by an high rate of spontaneous reporting [35].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that this percentage does not indicate the risk of ADRs for children taking part in RCTs but merely the proportion of trials in which ADRs were detected [6]. Previous studies have shown that the overall incidence of ADRs in the paediatric population is 634 per million children per year [24] and approximately 10% for hospitalised children [25]. It is important that ADRs are assessed in the setting of a trial so they can be established before the medicine is used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%